Efektivitas Daun Jeruk Kalamansi (Citrofortunella microcarpa) sebagai Insektisida Alami terhadap Kecoa (Periplaneta americana) - Lestari, Rena; Sutarno; Astuti, Annisa Puji; Parlindungan, Deni; Handayani, Dewi (Biotik, 2026)
Synthetic insecticides used to eradicate cockroaches leads to ecosystem damage and pest resistance, so there need environmental friendly natural insecticides. This study aims to evaluate the effectiveness of calamansi leaf extract (Citrofortunella microcarpa) as a natural insecticide against the American cockroach (Periplaneta americana). The leaves of C. microcarpa were extracted using the maceration method with 96% ethanol. The extract was prepared in 5 (five) concentrations: 20%, 40%, 60%, 80%, and 90%. Its effectiveness was tested using a spraying method and observed over 9 (nine) hours  on the trial. The data shows decreased in the activity of P. americana and morphological changes that ultimately led to death. Mortality data were analyzed using probit analysis to determine the LC₅₀ value. The phytochemical screening of leaf C. microcarpa extract revealed the presence of tannins, saponins, flavonoids, and alkaloids. The leaf C. microcarpa extract was effective in killing P. americana, with mortality rates of 33%, 83%, 100%, 100%, and 100% at concentrations of 20%, 40%, 60%, 80%, and 90%, respectively, and an LC₅₀ of 23.85%. Leaf C. Microcarpa extract containing tannins, saponins, flavonoids, and alkaloids. The 60% concentration demonstrated the highest effectiveness in increasing the mortality rate of P. americana. Keyword:Citrofortunella microcarpa; Periplaneta americana; Natural Insecticide; Mortality.